Method for preparing porous carbon based on synchronous synthesis of nitrile resin / graphene nanosheet and porous carbon material

Through a simultaneous synthesis method based on nitrile-based resin/graphene nanosheets, the problems of insufficient specific capacitance and poor cycle stability of bio-based porous carbon materials have been solved, and porous carbon materials with high specific capacitance and excellent cycle performance have been prepared.

CN119330339AActive Publication Date: 2025-01-21CHENGDU UNIV

Patent Information

Application Number
CN202411520214.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-21
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

The problem of insufficient specific capacitance of bio-based porous carbon materials and poor long-cycle stability.

Method used

A simultaneous synthesis method based on nitrile-based resin/graphene nanosheets was used to prepare porous carbon materials through ball milling, filtration washing and high-temperature carbonization steps. This method simultaneously achieves the synthesis of nitrile resin monomers and the crushing and dispersion of graphene nanosheets.

Benefits of technology

The prepared nitrile-based resin/graphene nanosheet porous carbon material has a high specific surface area, rich miscellaneous elements and excellent electrochemical properties. The maximum specific capacitance reaches 360F/g, excellent cycle performance, and the specific capacitance after 10,000 cycles The retention rate is still above 96%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330339A_ABST
    Figure CN119330339A_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing porous carbon based on synchronous synthesis of nitrile resin / graphene nanosheets and a porous carbon material, synthesis of nitrile resin and dispersion of graphene nanosheets are synchronously realized by means of a ball milling process, the synthesized nitrile resin is used as a carbon source, the graphene nanosheets are used as conductive reinforcements, and the porous carbon material is prepared. According to a certain component proportion, the nitrile resin doped graphene nanosheet porous carbon is prepared according to a certain heat treatment procedure. Based on synchronous synthesis of the nitrile resin / graphene nanosheets, functionalized utilization of nitrile resin and graphene is realized; the high carbon yield of the nitrile resin and the high conductivity of the graphene are utilized to improve the electrochemical performance of the prepared porous carbon. The obtained nitrile resin / graphene porous carbon has excellent electrochemical performance, is synthesized in one pot, not only integrates and optimizes the technological process, but also has the effect of '1 + 1 > 2', and has industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of porous carbon preparation, and specifically relates to a method for synchronously synthesizing nitrile-based resin / graphene nanosheets and preparing porous carbon. Background Art

[0002] The energy crisis, global warming and environmental pollution caused by the extensive use of fossil fuels have attracted great attention from the world. Supercapacitors are an important electrochemical energy storage device with fast charging and discharging capabilities, a wide operating temperature range, high power density and long service life. Supercapacitors are mainly composed of electrodes, diaphragms, electrolytes and current collectors, among which the electrode materials play a vital role in the electrochemical performance. Porous carbon materials are favored because of their rich preparation methods, excellent chemical stability, high specific surface area, adjustable pore size and excellent conductivity. It has been widely recognized as the preferred electrode material in energy storage and conversion devices such as supercapacitors, batteries and fuel cells. In addition, porous carbon has also shown its application potential in the field of environmental engineering, including in the adsorption of carbon dioxide, water purification and as a carrier for catalytic reactions. The realization of these applications is due to its unique physical and chemical properties, which makes it have broad application prospects in the fields of environmental governance and energy conversion.

[0003] At present, there are mainly two types of carbon sources for resin-based porous carbon: bio-based and petroleum-based. Patent CN110745823A discloses a method for preparing porous carbon using furfural resin as a carbon source. Although its carbon source comes from plants containing polypentose after a series of treatments and is widely present in many natural compounds, bio-based porous carbon still has problems such as the source of carbon precursors being greatly affected by regional differences, insufficient specific capacitance of carbon materials, and poor cycle stability.

[0004] In summary, a new method for preparing porous carbon materials is provided to improve the defects of insufficient specific capacitance and poor long-cycle stability of bio-based porous carbon materials in the above-mentioned related technologies. Summary of the invention

[0005] The purpose of the present invention is to provide a method for simultaneously synthesizing and preparing porous carbon based on nitrile resin / graphene nanosheets, which can improve the defects of insufficient specific capacitance and poor long-cycle stability of bio-based porous carbon materials.

[0006] In a first aspect, the present invention provides a method for preparing porous carbon based on simultaneous synthesis of nitrile-based resin / graphene nanosheets, comprising the following preparation steps:

[0007] S1. Reaction ball milling: weigh a phenol source, 4-nitrophthalonitrile or halogenated phthalonitrile, a weakly alkaline salt, a polar solvent, expanded graphite and grinding balls into a ball mill, and perform ball milling to obtain a reaction solution;

[0008] S2. Filtration and washing: The reaction solution is filtered for precipitation, the filtrate mixture is collected, and dilute hydrochloric acid is added to neutralize the weakly alkaline salt and then dried to prepare a nitrile resin / graphene nanosheets / halide salt mixture;

[0009] S3. High temperature carbonization: weigh the nitrile resin / graphene nanosheets / halide salt and weak alkaline salt and nitrile resin curing agent according to the ratio and mix them to obtain a mixture, calcine the mixture at a high temperature for carbonization, the calcination temperature is 500-1000°C, wash and dry after calcination to prepare porous carbon.

[0010] Optionally, in step S1, the phenol source includes at least one of bisphenol A, bisphenol S, bisphenol F, biphenyl, catechol, hydroquinone, resorcinol, biphenol, 2-aminophenol, 3-aminophenol, 4-aminophenol, and trisphenol; and / or,

[0011] The halogenated phthalonitrile comprises at least one of 2-chlorophthalonitrile, 2-bromophthalonitrile, 2-fluorophthalonitrile, 2-iodophthalonitrile, 3-chlorophthalonitrile, 3-bromophthalonitrile, 3-fluorophthalonitrile, 3-iodophthalonitrile, 4-chlorophthalonitrile, 4-bromophthalonitrile, 4-fluorophthalonitrile and 4-iodophthalonitrile; and / or,

[0012] The weakly alkaline salt includes at least one of potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, potassium bicarbonate, and sodium bicarbonate; and / or,

[0013] The polar solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N'N-dimethylformamide, and N'N-dimethylacetamide.

[0014] Optionally, in step S1, the ball milling reaction is carried out at 1000-9000 rpm for 10-120 hours.

[0015] Optionally, in step S1, 1 to 2 moles of 4-nitrophthalonitrile or halogenated phthalonitrile and 1 to 2 moles of weakly alkaline salt are used for every 1 mole of phenolic hydroxyl group, and the amount of the polar solvent used is 1 to 3 times the total mass of phenols, 4-nitrophthalonitrile or halogenated phthalonitrile and weakly alkaline salt.

[0016] Optionally, in step S3, the weakly alkaline salt includes at least one of potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, potassium bicarbonate, and sodium bicarbonate; and / or,

[0017] The curing agent of the nitrile-based resin includes at least one of 4'4-diaminodiphenyl sulfone, 4'4-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, 4-(4-aminophenoxy)phthalonitrile and 1,3-bis(4'-aminophenoxy)benzene.

[0018] Optionally, in step S3, the mass ratio of the nitrile resin / graphene nanosheets / halide salt and the weakly alkaline salt and the nitrile resin curing agent is 1:(0.01-0.1):(0.2-5):(0.2-5):(0.01-0.1).

[0019] Optionally, the pore structure of the porous carbon includes macropores, mesopores and micropores.

[0020] Optionally, the pore size of the macropore is 1-10 μm, the pore size of the mesopore is 2-10 nm, and the pore size of the micropore is less than 2 nm.

[0021] Optionally, the specific surface area of ​​the pore structure is 2500m 2 ·g -1 Above, the pore volume is 1.5cm 3 ·g -1 Below, the average pore diameter is 1.5 nm or less.

[0022] Optionally, the nitrogen content of the porous carbon is greater than 2%, and the nitrogen and oxygen element content is greater than 22%.

[0023] In a second aspect, the present invention provides a porous carbon material obtained by the aforementioned method for preparing porous carbon based on simultaneous synthesis of nitrile-based resin / graphene nanosheets.

[0024] In summary, the present invention has at least one of the following beneficial effects:

[0025] 1. The present invention adopts a one-pot synthesis method to simultaneously achieve the synthesis of nitrile resin monomers and the crushing and dispersion of graphene nanosheets, which is a two-pronged approach. The prepared nitrile resin / graphene nanosheet porous carbon material has a high specific surface area and rich and uniform impurity elements. The phthalonitrile resin-based porous carbon material prepared by the present invention has a specific surface area of ​​2500 m 2 ·g -1 Above, the pore volume is 1.5cm 3 ·g -1 The average pore size is less than 1.5nm, and the maximum specific surface area is 2579m 2 / g, pore volume 1.4cm 3 / g, the nitrogen content can reach up to 2.25%, and the impurity elements can reach up to 22.69%.

[0026] 2. The nitrile resin / graphene nanosheet porous carbon material prepared by the present invention can be used to prepare supercapacitor electrode materials, and has excellent electrochemical properties. In the three-electrode test, the maximum specific capacitance reaches 300F / g (1A / g) or more, and preferably 320F / g (1A / g) or more, and the highest reaches 360F / g (1A / g). It has excellent cycle performance, and after 10,000 cycles, the specific capacitance retention rate at 10A / g is more than 96%.

[0027] 3. The nitrile-based resin / graphene nanosheet porous carbon material of the present invention has a simple preparation process, low equipment cost, and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the infrared spectrum of the bisphenol A nitrile resin / graphene nanosheet porous carbon material prepared in Example 1.

[0029] Figure 2 This is a SEM image of the bisphenol A nitrile resin / graphene nanosheet porous carbon material prepared in Example 1.

[0030] Figure 3 This is a constant current charge / discharge curve (GCD) of the bisphenol A type nitrile resin / graphene nanosheet porous carbon material prepared in Example 1.

[0031] Figure 4 This is a BET result diagram of the resorcinol-type nitrile resin / graphene nanosheet porous carbon material prepared in Example 2.

[0032] Figure 5 This is an X-ray photoelectron spectroscopy (XPS) graph of the resorcinol-type nitrile resin / graphene nanosheet porous carbon material prepared in Example 2.

[0033] Figure 6 This is the cyclic stability of the three-electrode system of resorcinol-type nitrile resin / graphene nanosheet porous carbon material prepared in Example 2.

[0034] Figure 7 It is a line graph of the specific capacitance of the resorcinol-type nitrile-based resin / graphene nanosheet porous carbon material prepared in Example 2 and the resorcinol-type nitrile-based resin porous carbon material prepared in Comparative Example 1.

[0035] Figure 8 This is a line graph of the specific capacitance of the bisphenol F nitrile resin / graphene nanosheet porous carbon material prepared in Example 3. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing porous carbon by simultaneous synthesis of nitrile resin / graphene nanosheets. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] After a long period of research, it was found that nitrile-based resins are ideal candidate materials for manufacturing nitrogen-doped porous carbon because of their unique structure. The characteristic of nitrile-based resins is that there are two adjacent cyano groups on the benzene ring, which can be cured by addition into highly conjugated rigid nitrogen-rich heteroaromatic products, including phthalocyanine rings and triazine rings. These covalent heteroaromatic frameworks give nitrile-based resins a higher carbon residue rate, excellent thermal stability and thermal oxidation stability, excellent flame retardancy, good strong acid / alkali resistance, and high mechanical property retention rate at high temperatures. Therefore, nitrile-based resins are ideal substrates for realizing advanced porous materials. In addition, graphene has very excellent electrical conductivity, and its application in porous carbon materials will enhance the rapid transmission ability of electric charges, give it more outstanding electrical conductivity and electrochemical activity. Therefore, the one-pot synthesis of nitrile-based resins and graphene nanosheets not only shortens the process cycle, but also has performance gains. The present invention adopts a one-pot synthesis method to simultaneously realize the synthesis of nitrile-based resin monomers and the crushing and dispersion of graphene nanosheets, which is a two-pronged approach. The prepared nitrile-based resin / graphene nanosheet porous carbon material has a high specific surface area, rich and uniform impurity elements, and has a high maximum specific capacitance and excellent long-cycle stability in a three-electrode test. The present invention is obtained on the basis of this research.

[0038] In some embodiments of the present invention, the present invention provides a method for preparing porous carbon based on simultaneous synthesis of nitrile-based resin / graphene nanosheets, comprising the following preparation steps:

[0039] S1. Reaction ball milling: weigh a phenol source, 4-nitrophthalonitrile or halogenated phthalonitrile, a weakly alkaline salt, a polar solvent, expanded graphite and grinding balls into a ball mill, and perform ball milling to obtain a reaction solution;

[0040] S2. Filtration and washing: The reaction solution is filtered for precipitation, the filtrate mixture is collected, and dilute hydrochloric acid is added to neutralize the weakly alkaline salt and then dried to prepare a nitrile resin / graphene nanosheets / halide salt mixture;

[0041] S3. High temperature carbonization: weigh the nitrile resin / graphene nanosheets / halide salt and weak alkaline salt and nitrile resin curing agent according to the ratio and mix them to obtain a mixture, and subject the mixture to high temperature calcination and carbonization, the calcination temperature is 500-1000°C, and the mixture is washed and dried after calcination to prepare porous carbon; preferably, the calcination temperature is 550-850°C, and more preferably, the calcination temperature is 600-800°C; the calcination time is 0.5-10h, preferably 1-4h, the heating rate is 5-40°C / min, and the flow rate of argon is 50-200ml / min.

[0042] In some embodiments of the present invention, in step S1, the phenol source includes at least one of bisphenol A, bisphenol S, bisphenol F, biphenyl, catechol, hydroquinone, resorcinol, biphenol, 2-aminophenol, 3-aminophenol, 4-aminophenol, and trisphenol; preferably bisphenol A, bisphenol F and resorcinol; more preferably resorcinol; and / or,

[0043] The halogenated phthalonitrile comprises at least one of 2-chlorophthalonitrile, 2-bromophthalonitrile, 2-fluorophthalonitrile, 2-iodophthalonitrile, 3-chlorophthalonitrile, 3-bromophthalonitrile, 3-fluorophthalonitrile, 3-iodophthalonitrile, 4-chlorophthalonitrile, 4-bromophthalonitrile, 4-fluorophthalonitrile and 4-iodophthalonitrile; and / or,

[0044] The weakly alkaline salt includes at least one of potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, potassium bicarbonate, and sodium bicarbonate; and / or,

[0045] The polar solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N'N-dimethylformamide, and N'N-dimethylacetamide.

[0046] In some embodiments of the present invention, in step S1, the ball milling reaction is carried out at 1000-9000 rpm for 10-120 h; preferably, the ball milling speed is 2000-8000 rpm, more preferably 5000-8000 rpm; the ball milling time is preferably 15-80 h, more preferably 20-50 h.

[0047] In some embodiments of the present invention, in step S1, based on 1 unit mole of phenolic hydroxyl group, 1 to 2 unit moles of 4-nitrophthalonitrile or halogenated phthalonitrile and 1 to 2 unit moles of weakly alkaline salt are used, and the amount of the polar solvent used is 1 to 3 times the total mass of phenols, 4-nitrophthalonitrile or halogenated phthalonitrile and weakly alkaline salt.

[0048] In some embodiments of the present invention, in step S3, the weakly alkaline salt includes at least one of potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, potassium bicarbonate, and sodium bicarbonate; and / or,

[0049] The curing agent of the nitrile-based resin includes at least one of 4'4-diaminodiphenyl sulfone, 4'4-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, 4-(4-aminophenoxy)phthalonitrile and 1,3-bis(4'-aminophenoxy)benzene.

[0050] In some embodiments of the present invention, in step S3, the mass ratio of the nitrile resin / graphene nanosheets / halide salt and the weakly alkaline salt and the nitrile resin curing agent is 1: (0.01-0.1): (0.2-5): (0.2-5): (0.01-0.1); preferably 1: (0.01-0.04): (0.5-2): (0.2-5): (0.01-0.04); more preferably 1: (0.01-0.03): (0.5-2): (0.2-4): (0.01-0.04).

[0051] In some embodiments of the present invention, the porous carbon has a pore structure including macropores, mesopores and micropores. The pore size of the macropores is 1 to 10 μm, the pore size of the mesopores is 2 to 10 nm, and the pore size of the micropores is less than 2 nm. The specific surface area of ​​the pore structure is 2500 m 2 ·g -1 Above, the pore volume is 1.5cm 3 ·g -1 Below, the average pore diameter is 1.5 nm or less.

[0052] In some embodiments of the present invention, the nitrogen content of the porous carbon is greater than 2%, and the nitrogen and oxygen element content is greater than 22%.

[0053] The present invention is further described in detail below in conjunction with specific embodiments and drawings.

[0054] Example 1

[0055] Embodiment 1 provides a method for preparing porous carbon based on the simultaneous synthesis of bisphenol A type nitrile resin / graphene nanosheets, comprising the following preparation steps:

[0056] S1. Reaction ball milling: At room temperature, N-methylpyrrolidone (190 g), bisphenol A (18.05 g), potassium carbonate (23.75 g), 4-nitrophthalonitrile (27.39 g), expanded graphite (2 g) and zirconium oxide microspheres (diameter 0.2 mm and 2 mm, 33.33 g each) were added to a ball mill in sequence. The mixture was mixed for 36 h under high-speed stirring (7000 rpm) to obtain a reaction solution;

[0057] S2. Filtration and washing: pour the reaction solution into a sieve to precipitate, filter, collect the filtrate mixture, recover and wash the zirconium oxide microspheres for next use, adjust the pH of the filtrate mixture to 6-7 with 1 mol / L dilute hydrochloric acid, and then dry the filtrate mixture to obtain a bisphenol A type nitrile resin / graphene nanosheets / potassium chloride mixture. According to the ratio, the mass ratio of bisphenol A type nitrile resin: graphene nanosheets: potassium chloride is 1:0.02:1;

[0058] S3. High temperature carbonization: Mix and grind bisphenol A type nitrile resin: graphene nanosheets: potassium chloride: potassium carbonate: DDS (4'4-diaminodiphenyl sulfone) in a mass ratio of 1:0.02:1:2:0.02 for 30 minutes, then place the ground mixture in a quartz tube and put it into a tube furnace, calcining temperature is 600℃, calcining time is 2h, heating rate is 10℃ / min, argon flow rate is 100ml / min. After the calcined sample is rinsed with a certain amount of deionized water, rinsed until the pH of the washing liquid is about 7, and dried at 80℃ for 12h to obtain bisphenol A type nitrile resin / graphene nanosheet porous carbon material.

[0059] Figure 1 is the infrared spectrum of the bisphenol A nitrile resin / graphene nanosheet porous carbon prepared in Example 1. Figure 1 It can be seen that for the porous carbon sample obtained, -CN is at 2231 cm -1 The vibration peak intensity at 1517cm is very weak, indicating that the bisphenol A nitrile resin has been basically cured. -1 and 1355cm -1 The appearance of a new peak at 1715 cm reflects the formation of triazine ring structure during the polymerization of bisphenol A nitrile resin. In addition, it is worth noting that isoindoline (1715 cm -1 ) and phthalocyanine (966cm -1 ) is also the main product in the polymerization process. The above cured products indicate that there is cured bisphenol A type nitrile resin in the prepared porous carbon.

[0060] Figure 2 is a SEM image of the bisphenol A nitrile resin / graphene nanosheet porous carbon prepared in Example 1, Figure 2 The smooth part is bisphenol A nitrile resin, and the wrinkled part selected by the frame is the layered graphene sheet. It can be seen that the prepared porous carbon has a macroporous structure with a pore size of 1-10μm.

[0061] In order to further investigate the electrochemical performance of the bisphenol A nitrile resin / graphene nanosheet porous carbon material provided in Example 1, a three-electrode system was used for testing: a 10 mg / ml polytetrafluoroethylene N'N-dimethylacetamide solution was prepared, 80 mg of the dried bisphenol A nitrile resin / graphene nanosheet porous carbon material of Example 1, 10 mg of acetylene black, and 1 ml of a 10 mg / ml polytetrafluoroethylene N'N-dimethylacetamide solution were taken, ultrasonically mixed evenly, and 25 μl of the turbid solution was dropped on a 1*1 cm 2 The porous carbon electrode material was prepared by baking on carbon paper at 80°C for 12 hours, and then tested in a three-electrode system, with Hg / HgO electrode as the reference electrode, platinum electrode as the counter electrode, and 1M KOH as the electrolyte. The constant current charge / discharge curve (GCD diagram) of the porous carbon electrode material was measured on the electrochemical workstation. Figure 3 As shown, it was measured that at a current of 1 A / g, the specific capacitance of the porous carbon electrode material of Example 1 was as high as 300 F / g.

[0062] Example 2

[0063] Embodiment 2 provides a method for preparing porous carbon based on the simultaneous synthesis of resorcinol-type nitrile resin / graphene nanosheets, comprising the following preparation steps:

[0064] S1. Reaction ball milling: At room temperature, dimethyl sulfoxide (106 g), resorcinol (11 g), potassium carbonate (30 g), 4-chlorophthalonitrile (32.6 g), expanded graphite (2 g) and zirconium oxide microspheres (0.2 mm and 2 mm in diameter, 33.33 g each) were added to a ball mill in sequence. The mixture was mixed for 36 h under high-speed stirring (7000 rpm) to obtain a reaction solution;

[0065] S2. Filtration and washing: pour the reaction solution into a sieve to precipitate, filter, collect the filtrate mixture, recover and wash the zirconium oxide microspheres for next use, adjust the pH of the filtrate mixture to 6-7 with 1 mol / L dilute hydrochloric acid, and then dry the filtrate mixture to obtain a resorcinol-type nitrile resin / graphene nanosheets / potassium chloride mixture. According to the ratio, the mass ratio of resorcinol-type nitrile resin: graphene nanosheets: potassium chloride is 1:0.02:1;

[0066] S3. High temperature carbonization: Take the mass ratio of resorcinol-type nitrile resin: graphene nanosheets: potassium chloride: potassium hydroxide: DDS (4,4'-diaminodiphenyl sulfone) = 1:0.02:1:2:0.02 and mix and grind for 30 minutes, then put the ground mixture into a quartz tube and put it into a tube furnace, the calcination temperature is 600℃, the calcination time is 2h, the heating rate is 10℃ / min, and the flow rate of argon is 100ml / min. After the calcined sample is rinsed with a certain amount of deionized water, rinsed until the pH of the washing liquid is about 7, and dried at 80℃ for 12h to obtain the resorcinol-type nitrile resin / graphene nanosheet porous carbon material.

[0067] Using the same structural test characterization method as in Example 1, it was measured that the resorcinol-type nitrile resin / graphene nanosheet porous carbon material prepared in Example 2 contained cured resorcinol-type nitrile resin and layered graphene sheets, and the porous carbon prepared in Example 2 had a macroporous structure with a pore size of 1-10 μm. Figure 4 The BET characterization diagram of the resorcinol-based nitrile resin / graphene nanosheet porous carbon of Example 2 is shown in FIG. Figure 4 It can be seen that the pore structure of the resorcinol-based nitrile resin / graphene nanosheet porous carbon prepared in Example 2 also includes mesopores and micropores. Micropores are smaller than 2nm, and mesopores are larger than 2nm. Among them, the pore diameter of the micropores is mainly concentrated in the range of 0.3-1.5nm, while the mesopores are concentrated in the range of 2-4nm. The specific surface area of ​​the pore structure is measured to be 2579m 2 ·g -1 , pore volume 1.4cm 3 ·g -1 , the average pore size is 1.47nm.

[0068] The chemical element composition of the surface of the resorcinol-based nitrile resin / graphene nanosheet porous carbon material of Example 2 was tested by XPS. The XPS test results are as follows: Figure 5 The figure shows three peaks at 284.8eV (C1s), 541.8eV (O1s) and 400.8eV (N1s). Through semi-quantitative analysis, the nitrogen content is 2.25% and the nitrogen and oxygen element content reaches 22.69%, which has a positive effect on the electrochemical performance to a certain extent.

[0069] In order to further investigate the electrochemical performance of the resorcinol-based nitrile resin / graphene nanosheet porous carbon material provided in Example 2, the same electrochemical performance test method as in Example 1 was used to test in a three-electrode system: 10 mg / ml polytetrafluoroethylene N'N-dimethylacetamide solution was prepared, 80 mg of the dried resorcinol-based nitrile resin / graphene nanosheet porous carbon material of Example 2, 10 mg of acetylene black, and 1 ml of 10 mg / ml polytetrafluoroethylene N'N-dimethylacetamide solution were taken, ultrasonically mixed evenly, and 25 μl of the turbid solution was dropped on a 1*1 cm 2 The porous carbon electrode material was prepared by baking on carbon paper at 80°C for 12 hours, and then tested in a three-electrode system, with Hg / HgO electrode as the reference electrode, platinum electrode as the counter electrode, and 1M KOH as the electrolyte. The constant current charge / discharge curve of the porous carbon electrode material was measured on an electrochemical workstation. Figure 5 It can be seen from the figure that after 10,000 cycles, at 10 A / g, the specific capacitance retention rate of the porous carbon electrode material of Example 2 is above 96%. Figure 6 It can be seen that at a current of 1 A / g, the specific capacitance of the porous carbon electrode material of Example 2 is as high as 360 F / g.

[0070] Comparative Example 1

[0071] The difference between Comparative Example 1 and Example 2 is that Comparative Example 1 provides a method for preparing porous carbon based on resorcinol-type nitrile resin, comprising the following preparation steps:

[0072] S1. Reaction ball milling: At room temperature, dimethyl sulfoxide (106 g), resorcinol (11 g), potassium carbonate (30 g), 4-chlorophthalonitrile (32.6 g) and zirconium oxide microspheres (diameter 0.2 mm and 2 mm, 33.33 g each) were added to a ball mill in sequence. The mixture was mixed for 36 h under high-speed stirring (7000 rpm) to obtain a reaction solution;

[0073] S2. Filtration and washing: pour the reaction solution into a sieve to precipitate, filter, collect the filtrate mixture, recover and wash the zirconium oxide microspheres for next use, adjust the pH of the filtrate mixture to 6-7 with 1 mol / L dilute hydrochloric acid, and then dry the filtrate mixture to obtain a resorcinol-type nitrile resin / potassium chloride mixture. According to the ratio, the mass ratio of resorcinol-type nitrile resin: graphene nanosheets: potassium chloride is 1:1;

[0074] S3. High temperature carbonization: Mix and grind the mixture of resorcinol-type nitrile resin: potassium chloride: potassium hydroxide: DDS (4,4'-diaminodiphenyl sulfone) in a mass ratio of 1:1:2:0.02 for 30 minutes, then place the ground mixture in a quartz tube and put it into a tube furnace, calcining temperature is 600℃, calcining time is 2h, heating rate is 10℃ / min, argon flow rate is 100ml / min. After calcining, the sample is rinsed with a certain amount of deionized water until the pH of the washing liquid is about 7, and dried at 80℃ for 12h to obtain a porous carbon material of resorcinol-type nitrile resin.

[0075] The same method as in Example 2 was used to prepare a porous carbon electrode material using the resorcinol-based nitrile resin porous carbon material of Comparative Example 1, and the same test method as in Example 2 was used to measure the specific capacitance of the porous carbon electrode material of Comparative Example 1. Figure 6 As shown, at a current of 1 A / g, the specific capacitance of the porous carbon electrode material of Comparative Example 1 is 288 F / g. Combining the specific capacitances of the porous carbon electrode materials of Comparative Example 1 and Example 2, it can be seen that the synchronous generation of nitrile-based resin and graphene nanosheets is of great help in improving the electrochemical properties of porous carbon.

[0076] Example 3

[0077] Embodiment 3 provides a method for preparing porous carbon based on the simultaneous synthesis of bisphenol F-type nitrile resin / graphene nanosheets, comprising the following preparation steps:

[0078] S1. Reaction ball milling: At room temperature, N'N-dimethylformamide (120 g), bisphenol F (40 g), sodium bicarbonate (23.75 g), 4-chlorophthalonitrile (32.6 g), expanded graphite (2 g) and zirconium oxide microspheres (diameter 0.2 mm and 2 mm, 33.33 g each) were added to a ball mill in sequence. The mixture was mixed for 24 h under high-speed stirring (7000 rpm) to obtain a reaction solution;

[0079] S2. Filtration and washing: pour the reaction solution into a sieve to precipitate, filter, collect the filtrate mixture, recover and wash the zirconium oxide microspheres for next use, adjust the pH of the filtrate mixture to 6-7 with 1 mol / L dilute hydrochloric acid, and then dry the filtrate mixture to obtain a bisphenol F type nitrile resin / graphene nanosheets / sodium chloride mixture. According to the ratio, the mass ratio of bisphenol F type nitrile resin: graphene nanosheets: sodium chloride is 1:0.02:1;

[0080] S3. High temperature carbonization: Mix and grind bisphenol F type nitrile resin: graphene nanosheets: sodium chloride: potassium hydroxide: DDS (4,4'-diaminodiphenyl sulfone) at a mass ratio of 1:0.02:1:2:0.02 for 30 minutes, then place the ground mixture in a quartz tube and put it into a tube furnace, calcining at 700℃, calcining time of 2h, heating rate of 5℃ / min, argon flow rate of 100ml / min. After the calcined sample is rinsed with a certain amount of deionized water, rinsed until the pH of the washing solution is about 7, and dried at 80℃ for 12h to obtain bisphenol F type nitrile resin / graphene nanosheet porous carbon material.

[0081] Using the same structural test characterization method as in Example 1, it was found that the bisphenol F nitrile resin / graphene nanosheet porous carbon material prepared in Example 3 contained cured bisphenol F nitrile resin and layered graphene sheets, and the porous carbon prepared in Example 3 had a macroporous structure with a pore size of 1-10 μm.

[0082] The same method as in Example 1 was used to prepare a porous carbon electrode material using the bisphenol F type nitrile resin / graphene nanosheet porous carbon material of Example 3, and the same test method as in Example 1 was used to measure the GCD diagram of the porous carbon electrode material of Example 3. Figure 7 As shown, it was measured that the specific capacitance of the porous carbon electrode material of Example 3 was 321 F / g at a current of 1 A / g.

[0083] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to this application.

Claims

1. A method for preparing porous carbon based on simultaneous synthesis of nitrile resin / graphene nanosheets, characterized in that: The method comprises the following preparation steps: S1. Reaction ball milling: weigh a phenol source, 4-nitrophthalonitrile or halogenated phthalonitrile, a weakly alkaline salt, a polar solvent, expanded graphite and grinding balls into a ball mill, and perform ball milling to obtain a reaction solution; S2. Filtration and washing: The reaction solution is subjected to precipitation filtration, the filtrate mixture is collected, and dilute hydrochloric acid is added to neutralize the weakly alkaline salt and then dried to prepare a nitrile resin / graphene nanosheets / halide salt mixture; S3. High temperature carbonization: weigh the nitrile resin / graphene nanosheets / halide salt and weak alkaline salt and nitrile resin curing agent according to the ratio and mix them to obtain a mixture, calcine the mixture at a high temperature for carbonization, the calcination temperature is 500-1000°C, wash with water and dry after calcination to prepare porous carbon.

2. The method for preparing porous carbon based on simultaneous synthesis of nitrile resin / graphene nanosheets according to claim 1, characterized in that: In step S1, the phenol source includes at least one of bisphenol A, bisphenol S, bisphenol F, biphenyl, catechol, hydroquinone, resorcinol, biphenol, 2-aminophenol, 3-aminophenol, 4-aminophenol, and trisphenol; and / or, The halogenated phthalonitrile comprises at least one of 2-chlorophthalonitrile, 2-bromophthalonitrile, 2-fluorophthalonitrile, 2-iodophthalonitrile, 3-chlorophthalonitrile, 3-bromophthalonitrile, 3-fluorophthalonitrile, 3-iodophthalonitrile, 4-chlorophthalonitrile, 4-bromophthalonitrile, 4-fluorophthalonitrile and 4-iodophthalonitrile; and / or, The weakly alkaline salt includes at least one of potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, potassium bicarbonate, and sodium bicarbonate; and / or, The polar solvent includes at least one of dimethyl sulfoxide, N-methylpyrrolidone, N'N-dimethylformamide, and N'N-dimethylacetamide.

3. The method for preparing porous carbon based on simultaneous synthesis of nitrile resin / graphene nanosheets according to claim 1 or 2, characterized in that: In step S1, the ball milling reaction is carried out at 1000-9000 rpm for 10-120 hours.

4. The method for preparing porous carbon based on simultaneous synthesis of nitrile resin / graphene nanosheets according to claim 1 or 2, characterized in that: In step S3, the weakly alkaline salt includes at least one of potassium carbonate, sodium carbonate, potassium hydroxide, sodium hydroxide, potassium bicarbonate, and sodium bicarbonate; and / or, The curing agent of the nitrile-based resin includes at least one of 4'4-diaminodiphenyl sulfone, 4'4-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, 4-(4-aminophenoxy)phthalonitrile and 1,3-bis(4'-aminophenoxy)benzene.

5. The method for preparing porous carbon based on simultaneous synthesis of nitrile resin / graphene nanosheets according to claim 1 or 2, characterized in that: In step S3, the mass ratio of the nitrile resin / graphene nanosheets / halide salt and the weakly alkaline salt and the nitrile resin curing agent is 1:(0.01-0.1):(0.2-5):(0.2-5):(0.01-0.1).

6. The method for preparing porous carbon based on simultaneous synthesis of nitrile resin / graphene nanosheets according to claim 1, characterized in that: The pore structure of the porous carbon includes macropores, mesopores and micropores.

7. The method for preparing porous carbon based on simultaneous synthesis of nitrile resin / graphene nanosheets according to claim 6, characterized in that: The pore size of the macropore is 1-10 μm, the pore size of the mesopore is 2-10 nm, and the pore size of the micropore is less than 2 nm.

8. The method for preparing porous carbon based on simultaneous synthesis of nitrile resin / graphene nanosheets according to claim 6 or 7, characterized in that: The specific surface area of ​​the pore structure is 2500m 2 ·g -1 Above, the pore volume is 1.5cm 3 ·g -1 Below, the average pore diameter is 1.5 nm or less.

9. The method for preparing porous carbon based on simultaneous synthesis of nitrile resin / graphene nanosheets according to claim 1, characterized in that: The porous carbon has a nitrogen content of more than 2%, and a nitrogen and oxygen element content of more than 22%.

10. A porous carbon material obtained by the method for preparing porous carbon based on simultaneous synthesis of nitrile-based resin / graphene nanosheets as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of furfural resin-based porous carbon electrode material for super capacitor

    CN110745823A

  • Method for preparing polymer / graphene composite material

    CN101864005A

  • Nitrogen-doped carbon nanometer conductive network / sulfur composite material and preparation method and application thereof

    CN107240679A

  • Preparation of GrapheneConducting Polymer Composite Electrode Materials by Mechanochemical Polymerization

    CN109192539A

  • Method for preparing porous carbon hybrid material based on graphite and polyhalogenated hydrocarbon and energy storage application of porous carbon hybrid material

    CN109686579A

Cited By

  • Preparation method of graphene oxide modified phthalonitrile resin

    CN120442046A

  • Methods for obtaining porous electrode material and methods for obtaining a felt with porous electrode material

    EP4813910A1